Difference between revisions of "Abstract Algebra: Groups"

From Department of Mathematics at UTSA
Jump to navigation Jump to search
 
(One intermediate revision by the same user not shown)
Line 21: Line 21:
 
<p>Clearly <span class="math-inline"><math>a * (b * c) \neq (a * b) * c</math></span> so <span class="math-inline"><math>\mathbb{Z}</math></span> does not form a group under the operation <span class="math-inline"><math>*</math></span>.</p>
 
<p>Clearly <span class="math-inline"><math>a * (b * c) \neq (a * b) * c</math></span> so <span class="math-inline"><math>\mathbb{Z}</math></span> does not form a group under the operation <span class="math-inline"><math>*</math></span>.</p>
  
===Cancellation Law===
+
==Basic Theorems Regarding Groups==
 +
<p>Recall that a group <span class="math-inline"><math>(G, \cdot)</math></span> is a set <span class="math-inline"><math>G</math></span> with a binary operation <span class="math-inline"><math>\cdot</math></span> such that:</p>
 +
<ul>
 +
<li><strong>1)</strong> <span class="math-inline"><math>\cdot</math></span> is associative, i.e., for all <span class="math-inline"><math>a, b, c \in G</math></span>, <span class="math-inline"><math>a \cdot (b \cdot c) = (a \cdot b) \cdot c)</math></span>.</li>
 +
</ul>
 +
<ul>
 +
<li><strong>2)</strong> There exists an identity element <span class="math-inline"><math>e \in G</math></span> such that <span class="math-inline"><math>a \cdot e = a = e \cdot a</math></span> for all <span class="math-inline"><math>a \in G</math></span>.</li>
 +
</ul>
 +
<ul>
 +
<li><strong>3)</strong> For each <span class="math-inline"><math>a \in G</math></span> there exists an <span class="math-inline"><math>a^{-1} \in G</math></span> such that <span class="math-inline"><math>a \cdot a^{-1} = a^{-1} \cdot a = e</math></span>.</li>
 +
</ul>
 +
<p>We will now look at some rather basic results regarding groups which we can derive from the group axioms above.</p>
 +
<blockquote style="background: white; border: 1px solid black; padding: 1em;">
 +
<td><strong>Proposition 1:</strong> Let <span class="math-inline"><math>(G, \cdot)</math></span> be a group and let <span class="math-inline"><math>e</math></span> be the identity for this group. Then:<br />
 +
<strong>a)</strong> The identity element <span class="math-inline"><math>e \in G</math></span> is unique.<br />
 +
<strong>b)</strong> For each <span class="math-inline"><math>a \in G</math></span>, the corresponding inverse <span class="math-inline"><math>a^{-1} \in G</math></span> is unique.<br />
 +
<strong>c)</strong> For each <span class="math-inline"><math>a \in G</math></span>, <span class="math-inline"><math>(a^{-1})^{-1} = a</math></span>.<br />
 +
<strong>d)</strong> For all <span class="math-inline"><math>a, b \in G</math></span>, <span class="math-inline"><math>(a \cdot b)^{-1} = b^{-1} \cdot a^{-1}</math></span>.<br />
 +
<strong>e)</strong> For all <span class="math-inline"><math>a, b \in G</math></span>, if <span class="math-inline"><math>a \cdot b = e</math></span> then <span class="math-inline"><math>a = b^{-1}</math></span> and <span class="math-inline"><math>b = a^{-1}</math></span>.<br />
 +
<strong>f)</strong> If <span class="math-inline"><math>a^2 = a</math></span> then <span class="math-inline"><math>a = e</math></span>.</td>
 +
</blockquote>
 +
<ul>
 +
<li><strong>Proof of a)</strong> Suppose that <span class="math-inline"><math>e</math></span> and <span class="math-inline"><math>e'</math></span> are both identities for <span class="math-inline"><math>\cdot</math></span>. Then:</li>
 +
</ul>
 +
<div style="text-align: center;"><math>\begin{align} \quad e = e \cdot e = e \cdot e' = e' \cdot e' = e' \end{align}</math></div>
 +
<ul>
 +
<li>Therefore <span class="math-inline"><math>e = e'</math></span> so the identity for <span class="math-inline"><math>\cdot</math></span> is unique. <span class="math-inline"><math>\blacksquare</math></span></li>
 +
</ul>
 +
<ul>
 +
<li><strong>Proof of b)</strong> Suppose that <span class="math-inline"><math>a^{-1} \in G</math></span> and <span class="math-inline"><math>a^{-1'} \in G</math></span> are both inverses for <span class="math-inline"><math>a \in G</math></span> under <span class="math-inline"><math>\cdot</math></span>. Then:</li>
 +
</ul>
 +
<div style="text-align: center;"><math>\begin{align} \quad a^{-1} = a^{-1} \cdot e = a^{-1} \cdot (a \cdot a^{-1'}) = (a^{-1} \cdot a)*a^{-1} = e \cdot a^{-1'} = a^{-1'} \end{align}</math></div>
 +
<ul>
 +
<li>Therefore <span class="math-inline"><math>a^{-1} = a^{-1'}</math></span> so the inverse for <span class="math-inline"><math>a</math></span> is unique. <span class="math-inline"><math>\blacksquare</math></span></li>
 +
</ul>
 +
<ul>
 +
<li><strong>Proof of c)</strong> Let <span class="math-inline"><math>a \in G</math></span>. Then <span class="math-inline"><math>(a^{-1})^{-1}</math></span> is the inverse to <span class="math-inline"><math>a^{-1}</math></span>. However, the inverse to <span class="math-inline"><math>a^{-1}</math></span> is <span class="math-inline"><math>a</math></span> and by (b) we have shown that the inverse of each element in <span class="math-inline"><math>G</math></span> is unique. Therefore <span class="math-inline"><math>a = (a^{-1})^{-1}</math></span>. <span class="math-inline"><math>\blacksquare</math></span></li>
 +
</ul>
 +
<ul>
 +
<li><strong>Proof of d)</strong> If we apply the operation <span class="math-inline"><math>\cdot</math></span> between <span class="math-inline"><math>b^{-1} \cdot a^{-1}</math></span> and <span class="math-inline"><math>(a \cdot b)</math></span> we get:</li>
 +
</ul>
 +
<div style="text-align: center;"><math>\begin{align} \quad (a \cdot b) \cdot [b^{-1} \cdot a^{-1}] & = a \cdot [(b \cdot b^{-1}) \cdot a^{-1}] \\ \quad &= a \cdot [e \cdot a^{-1}] \\ \quad &= a \cdot a^{-1} \\ \quad &= e \end{align}</math></div>
 +
<ul>
 +
<li>Therefore the inverse of <span class="math-inline"><math>(a \cdot b)</math></span> is <span class="math-inline"><math>b^{-1} \cdot a^{-1}</math></span>. We also have that the invere of <span class="math-inline"><math>(a \cdot b)</math></span> is <span class="math-inline"><math>(a \cdot b)^{-1}</math></span>. By (b), the inverse of <span class="math-inline"><math>(a \cdot b)</math></span> is unique and so:</li>
 +
</ul>
 +
<div style="text-align: center;"><math>\begin{align} \quad (a \cdot b)^{-1} = b^{-1} \cdot a^{-1} \quad \blacksquare \end{align}</math></div>
 +
<ul>
 +
<li><strong>Proof of e)</strong> Suppose that <span class="math-inline"><math>a \cdot b = e</math></span>. Then:</li>
 +
</ul>
 +
<div style="text-align: center;"><math>\begin{align} \quad a \cdot b &= e \\ \quad (a \cdot b) \cdot b^{-1} &= e \cdot b^{-1} \\ \quad a \cdot (b \cdot b^{-1}) &= b^{-1} \\ \quad a \cdot e &= b^{-1} \\ \quad a &= b^{-1} \end{align}</math></div>
 +
<ul>
 +
<li>Similarly:</li>
 +
</ul>
 +
<div style="text-align: center;"><math>\begin{align} \quad a \cdot b &= e \\ \quad a^{-1} \cdot (a \cdot b) &= a^{-1} \cdot e \\ \quad (a^{-1} \cdot a) \cdot b &= a^{-1} \\ \quad e \cdot b &= a^{-1} \\ \quad b &= a^{-1} \quad \blacksquare \end{align}</math></div>
 +
<ul>
 +
<li><strong>Proof of f)</strong> Suppose that <span class="math-inline"><math>a^2 = a \cdot a = a</math></span>. Then:</li>
 +
</ul>
 +
<div style="text-align: center;"><math>\begin{align} \quad a^2 &= a \\ \quad a \cdot a &= a \\ \quad a^{-1} \cdot (a \cdot a) &= a^{-1} \cdot a \\ \quad (a^{-1} \cdot a) \cdot a &= e \\ \quad e \cdot a &= e \\ \quad a &= e \end{align}</math></div>
 +
<ul>
 +
<li>Hence <span class="math-inline"><math>a = e</math></span>. Alternatively we see that if <span class="math-inline"><math>a \cdot a = a</math></span> then the inverse of <span class="math-inline"><math>a</math></span> with respect to <span class="math-inline"><math>\cdot</math></span> is <span class="math-inline"><math>e</math></span>, that is <span class="math-inline"><math>a^{-1} = e</math></span>. Multiplying both sides of this equation by <span class="math-inline"><math>a</math></span> gives us that <span class="math-inline"><math>a = e</math></span>. <span class="math-inline"><math>\blacksquare</math></span></li>
 +
</ul>
 +
 
 +
 
 +
==Cancellation Law==
 
<p>We will now look at another important property of groups called the cancellation law.</p>
 
<p>We will now look at another important property of groups called the cancellation law.</p>
 
<blockquote style="background: white; border: 1px solid black; padding: 1em;">
 
<blockquote style="background: white; border: 1px solid black; padding: 1em;">
Line 36: Line 99:
 
<p>It is very important to note that the cancellation law holds with regards to the operation <span class="math-inline"><math>\cdot</math></span> for any group <span class="math-inline"><math>(G, \cdot)</math></span>. We will see that the cancellation law does not necessarily hold with respect to an operation on a set when we look at algebraic structures with two defined operations.</p>
 
<p>It is very important to note that the cancellation law holds with regards to the operation <span class="math-inline"><math>\cdot</math></span> for any group <span class="math-inline"><math>(G, \cdot)</math></span>. We will see that the cancellation law does not necessarily hold with respect to an operation on a set when we look at algebraic structures with two defined operations.</p>
 
<p>It is also important to note that if <span class="math-inline"><math>a \cdot b = c \cdot a</math></span> or <span class="math-inline"><math>b \cdot a = a \cdot c</math></span> then we cannot necessarily deduce that <span class="math-inline"><math>b = c</math></span> because we would then require the additional property that <span class="math-inline"><math>\cdot</math></span> is commutative which is not one of the group axioms (but instead one of the Abelian group axioms).</p>
 
<p>It is also important to note that if <span class="math-inline"><math>a \cdot b = c \cdot a</math></span> or <span class="math-inline"><math>b \cdot a = a \cdot c</math></span> then we cannot necessarily deduce that <span class="math-inline"><math>b = c</math></span> because we would then require the additional property that <span class="math-inline"><math>\cdot</math></span> is commutative which is not one of the group axioms (but instead one of the Abelian group axioms).</p>
 +
 +
== Licensing ==
 +
Content obtained and/or adapted from:
 +
* [http://mathonline.wikidot.com/abstract-algebra Abstract Algebra, mathonline.wikidot.com] under a CC BY-SA license

Latest revision as of 14:28, 19 November 2021

Recall that an operation on is said to be associative if for all we have that and is said to be commutative if for all we have that .

An element is the identity element of under if for all we have that and .

We can now begin to describe our first type of algebraic structures known as groups, which are a set equipped with a binary operation that is associative, contains an identity element, and contains inverse elements under for each element in .

Definition: A Group is a pair where is a set and is a binary operation on with the following properties:

1. For all , (Associativity of ).
2. There exists an such that for all , and (The existence of an Identity Element).
3. For all there exists an such that and (The existence of inverses).

Furthermore, if is a finite set then the group is said to be a Finite Group and if is an infinite set then the group is said to be an Infinite Group. More generally, the Order of (or **Size of ) is the size of and is denoted .

When we use the multiplication symbol to denote the operation on , we often call a “multiplicative group”. When the operation of the group is instead denoted by (instead of ) then we often call an “additive group”, and we write the inverse of each as (instead of ).

Some of the sets and binary operations we have already seen can be considered groups. For example, is a group under standard addition since the sum of any two real numbers is a real number, , is associative, an additive identity exists and inverse elements exist for every (namely ).

Furthermore, is also a group under the operation of standard addition since the sum of any two integers is an integer, addition is associative, the additivity identity is , and for all we have as additive inverses.

We will examine many other (more interesting) groups later on, but for now, let's look at an example of a set and a binary operation that does NOT form a group.

Example 1

Consider the set of integers and define for all by:

(Where the on the righthand side is usual addition of numbers). We will show that is NOT a group by showing that is not associative. Let . Then is not associative since:

Clearly so does not form a group under the operation .

Basic Theorems Regarding Groups

Recall that a group is a set with a binary operation such that:

  • 1) is associative, i.e., for all , .
  • 2) There exists an identity element such that for all .
  • 3) For each there exists an such that .

We will now look at some rather basic results regarding groups which we can derive from the group axioms above.

Proposition 1: Let be a group and let be the identity for this group. Then:

a) The identity element is unique.
b) For each , the corresponding inverse is unique.
c) For each , .
d) For all , .
e) For all , if then and .

f) If then .

  • Proof of a) Suppose that and are both identities for . Then:
  • Therefore so the identity for is unique.
  • Proof of b) Suppose that and are both inverses for under . Then:
  • Therefore so the inverse for is unique.
  • Proof of c) Let . Then is the inverse to . However, the inverse to is and by (b) we have shown that the inverse of each element in is unique. Therefore .
  • Proof of d) If we apply the operation between and we get:
  • Therefore the inverse of is . We also have that the invere of is . By (b), the inverse of is unique and so:
  • Proof of e) Suppose that . Then:
  • Similarly:
  • Proof of f) Suppose that . Then:
  • Hence . Alternatively we see that if then the inverse of with respect to is , that is . Multiplying both sides of this equation by gives us that .


Cancellation Law

We will now look at another important property of groups called the cancellation law.

Theorem 1 (The Cancellation Law for Groups): Let be a group and let . If or then .

  • Proof: Let denote the inverse of under . Suppose that . Then:
  • Similarly, suppose now that . Then:

It is very important to note that the cancellation law holds with regards to the operation for any group . We will see that the cancellation law does not necessarily hold with respect to an operation on a set when we look at algebraic structures with two defined operations.

It is also important to note that if or then we cannot necessarily deduce that because we would then require the additional property that is commutative which is not one of the group axioms (but instead one of the Abelian group axioms).

Licensing

Content obtained and/or adapted from: